Early Administration of Therapeutic Anticoagulation Following Intravenous Thrombolysis for Acute Cardiogenic Embolic Stroke Caused by Left Ventricular Thrombus: Case Report and Topic Review - Gill, Rick; Donahey, Elisabeth; Ruland, Sean (Frontiers in Neurology, 2015)
Cardiogenic cerebral embolism represents 20% of all acute ischemic strokes with one third of these being caused by left ventricular thrombus (LVT). LVT is not a contraindication for treatment with intravenous recombinant tissue plasminogen activator (IV rtPA) for acute ischemic stroke (AIS). However the subsequent treatment of a potentially unstable LVT is contraindicated for 24 hours following the use of IV rtPA according to current guidelines. We present a 66-year-old man with AIS treated with IV rtPA. Echocardiogram shortly after treatment demonstrated both a large apical and septal thrombus in the left ventricle and at 12 hours post IV rtPA infusion, therapeutic anticoagulation with heparin was started without complication. In practice, the action of IV rtPA outlasts its apparent half-life because of thrombin-binding and the prolonged effects and longer half-life of its product, plasmin, however the pharmacokinetics do not warrant prolonged avoidance of therapeutic anticoagulation when clinically indicated. Our case demonstrates that anticoagulation for potentially unstable LVT can be safely initiated at 12 hours following IV rtPA treatment for AIS.